PENGEMBANGAN MEDIA PEMBELAJARAN PAI BERBASIS VIDEO PADA MATERI SURAH AL-FIIL - Rusmayani Rusmayani; Haris Nursyah Arifin; Mohamad Aso Samsudin; Nur Azizah (Fakultas Tarbiyah, Universitas Ibrahimy, 2023)
The development of this media stems from a lack of understanding of Muslim students at SD No. 3 Jimbaran regarding short surah material, especially surah Al-Fīl. The purpose of this study was to determine the feasibility of instructional video media for learning PAI material for surah Al-Fīl. The method used is Research and Development (R&D) using the ADDIE model with data search stages through observation and preparation of questionnaire instruments. The results of the validation of material experts with a percentage of 99.2%, design experts with a percentage of 86.07%, media experts with a percentage of 91.30%, individual tests with a percentage of 83.33%, small group tests with a percentage of 84.99% and group tests large with a percentage of 84.18%. Based on the average of the three experts, the results of the percentage were 92.19% in the very feasible category and the average of the three groups of students got the percentage of 84.16% in the very feasible category. It can be concluded from the results of these percentages that the product developed is very suitable to be used as a medium for learning PAI.